Wild mammals in transformed landscapes: report on the 26th Theriological School (Khortytsia, 2019) - Kateryna Ocheretna; Nataliia Lebedieva; Mariia Polzyk (Theriologia Ukrainica, 2019)
The ХХVI Theriological School "Wild Mammals in Transformed Landscapes" held on 17–21 June 2019 was organised by the National Museum of Natural History NAS of Ukraine, Department of Forest Biology, Game Management and Ichthyology of Zaporizhzhia National University, and the National Reserve "Khortytsia". More than 37 zoologists representing 23 institutions of four countries such as Ukraine, Belarus, Poland, and France took part in the conference. This School-Seminar consisted of several thematic blocks: keynote session, thematic reports and discussions on the main topic, current research and approbation of theses results, workshops and field studies, "Bat Night" event and photo contest "The Boar and Its Family in the Lens". The program of the School was fully implemented. Workshops on collecting and analysis of pellets and on in vivo study methods of bats revealed new species in the mammal fauna of Khortytsya Island, in particular Mus spicilegus, Sylvaemus tauricus and Pipistrellus nathusii, and also confirmed the presence of a number of other species of shrews, bats and rodents. The Dniester Canyon National Nature Park was chosen as the venue of the next Theriological School in autumn 2020. Also, the leadership of the Theriological Society decided to hold an inter-school seminar "Mammals in Pellets of Birds of Prey" in autumn or winter of 2019 in Kamianets-Podilskyi.